2009
DOI: 10.1039/b819874h
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic gasification of algae in supercritical water for biofuel production and carbon capture

Abstract: There has been growing concern about the way cultivating biomass for the production of agro-biofuels competes with food production. To avoid this competition biomass production for biofuels will, in the long term, have to be completely decoupled from food production. This is where microalgae have enormous potential. Here we propose a novel process based on microalgae cultivation using dilute fossil CO 2 emissions and the conversion of the algal biomass through a catalytic hydrothermal process. The resulting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(114 citation statements)
references
References 32 publications
(38 reference statements)
4
109
0
1
Order By: Relevance
“…Alternatively, microalgae grow in freshwater/marine systems and there is no requirement for land, which has been gradually recognized as potential feedstocks for the next generation of biofuels and chemical (Williams and Laurens, 2010;Anastasakis and Ross, 2011;López-González et al, 2014). Several possible pathways for converting microalgae to bioenergy have been investigated, mainly including biochemical conversion like anaerobic digestion and alcoholic fermentation, thermochemical conversion such as combustion, pyrolysis, gasification and liquefaction (Rizzo et al, 2013;Gai et al, 2014;Stucki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, microalgae grow in freshwater/marine systems and there is no requirement for land, which has been gradually recognized as potential feedstocks for the next generation of biofuels and chemical (Williams and Laurens, 2010;Anastasakis and Ross, 2011;López-González et al, 2014). Several possible pathways for converting microalgae to bioenergy have been investigated, mainly including biochemical conversion like anaerobic digestion and alcoholic fermentation, thermochemical conversion such as combustion, pyrolysis, gasification and liquefaction (Rizzo et al, 2013;Gai et al, 2014;Stucki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gasification of Spirulina to a methane-rich syngas using supercritical water and ruthenium catalysts has been predicted to yield up to 60-70 % of the heating value contained in the microalgal biomass (Stucki et al 2009). Experimental studies on SCWG at 550 °C of Nannochloropsis found energy conversion of biomass to syngas of up to 60 % (Guan et al 2012a).…”
Section: Gasification Of Microalgaementioning
confidence: 99%
“…The second technique is via the hydrothermal liquefaction (HTL) pathway that produces a water-insoluble bio-crude oil by using treatments at high pressure (5-20 MPa) 57 and at the temperature range of 250-450°C [7,8]. Other techniques, such as pyrolysis [9] and gasification [10,11], were also applied for converting algae to biofuels. However, these techniques have not been extensively studied yet, because of their inherent problems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an integrated biorefinery process for ALU pathway was established [6]. The second technique is via the hydrothermal liquefaction (HTL) pathway that produces a water-insoluble bio-crude oil by using treatments at high pressure (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and at the temperature range of 250-450°C [7,8]. Other techniques, such as pyrolysis [9] and gasification [10,11], were also applied for converting algae to biofuels.…”
Section: Introductionmentioning
confidence: 99%